Fault Detection in Modular Offshore Platform Connections Using Extended Kalman Filter - Tockner, Andreas; Blümel, Bernhard; Ellermann, Katrin (Frontiers in Built Environment, 2021)
Within the Space@Sea project, funded by the Horizon 2020 program, a concept for a floating island was developed. The main idea is to create space in the offshore environment, which can be used to harvest renewable energy, grow food or build a maritime transport and logistic hub. The island is designed as an assembly of platforms, which are connected by ropes and fenders. These connection elements are considered critical, as they have to carry extreme loads in the sever offshore environment. At the same time any failure in the connecting elements might put the entire platform structure at risk. This paper presents a feasibility study for the fault detection in the connection elements using Extended Kalman filter. For various test cases, typical parameters of the connecting elements are estimated from motion data of the structure. Thus, the technique reveals changes in the connections. For various test cases, it is shown that fault detection is possible. Not only a failure of a single connecting rope but also multiple faults in the system can be detected.